The neuropharmacology of upper airway motor control in the awake and asleep states: implications for obstructive sleep apnoea - Horner, Richard L (BioMed Central, 2001)
Obstructive sleep apnoea is a common and serious breathing problem that is caused by effects of sleep on pharyngeal muscle tone in individuals with narrow upper airways. There has been increasing focus on delineating the brain mechanisms that modulate pharyngeal muscle activity in the awake and asleep states in order to understand the pathogenesis of obstructive apnoeas and to develop novel neurochemical treatments. Although initial clinical studies have met with only limited success, it is proposed that more rational and realistic approaches may be devised for neurochemical modulation of pharyngeal muscle tone as the relevant neurotransmitters and receptors that are involved in sleep-dependent modulation are identified following basic experiments.